Public awareness, knowledge and practice relating to epilepsy amongst adult residents in rural Cameroon - case study of the Fundong health district - Bain, Luchuo Engelbert (The African Field Epidemiology Network, 2013)
INTRODUCTION: Epilepsy associated stigma remains a main hindrance to epilepsy care, especially in developing countries. In Africa, anti-epileptic drugs are available, affordable and effective. As of now, no community survey on epilepsy awareness and attitudes has been reported from this area Cameroon with a reported high prevalence of epilepsy. METHODS: To contribute data to the elaboration of the National Epilepsy Control Programme, we carried out a cross-sectional descriptive community survey of 520 households. We had as main objective to obtain baseline data on the knowledge, attitudes and practice of adults towards epilepsy in rural Cameroon, and compare with existing data. RESULTS: Most respondents had heard or read about epilepsy, knew someone who had epilepsy and had seen someone having a seizure. The most frequently cited cause of epilepsy was witchcraft. Most subjects believed epilepsy is contagious. Epilepsy was a form of madness or insanity to 33.5% of them. Only 54.9% of respondents would meet a medical doctor for the treatment. Most respondents would not permit equal employment opportunities, association and child's marriage to someone with epilepsy. Age, female sex and level of education were associated to negative attitudes (p<0.001). CONCLUSION: Adults in Fundong are very acquainted with epilepsy but have many erroneous beliefs about the condition. Their attitudes are generally negative. The National Epilepsy Programme must insist on modes of transmission, treatment options and first aid measures during epileptic seizures. The elderly (>50 years) and those without any formal education should be the main targets during health information, education and communication programmes.